PERANAN VISUM ET REPERTUM DALAM MEMBANTU PROSES TUNTUTAN PIDANA TERHADAP KASUS PENGANIAYAAN - Sekar Wijayanti (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTThis research was conducted at Polres Samarinda Kelurahan kunjang River, District Samarinda, East Kalimantan Province. This research was conducted by taking data and interviewing with the concerned parties namely Head of Criminal Investigation Unit of Samarinda and Penidik Police in Unit of Protection of Women and Child (PPA) of Samarinda Police.The results showed that the presence of visum et repertum is needed in every devotion of rape crime in this case visum et repertum always be evidence in rape criminal investigation, visum et repertum has a very important function for investigators especially to know the existence of elements of intercourse and elements of violence that occur in the victim, visum et repertum is one of the most important evidence to help investigators conduct further investigation and become one of the evidences that must always exist in every rape case examination until the stage of the trial and if the results visum et repertum does not contain any sign of violence or threats of violence against the victim, it will be carried out a series of actions or attempts by the investigator to prove and find the existence of elements of violence or threat of violence, the action referred to the summon of the suspect and the victim, the examination and confiscation of objects which may be evidence of a crime of rape and if necessary examination of the Place of Genesis Case (TKP).